Approach avoidance training to curb consumption of sugar-sweetened beverages: a pilot randomized controlled trial in healthy volunteers - Vögtle, Elisabeth; Dombret, Sophia; Bonabi, Anahita; Friederich, Hans-Christoph; Brockmeyer, Timo (Appetite, 2021)
Elevated consumption of sugar-sweetened beverages (SSBs) contributes to overweight and obesity. Automatic action tendencies like an approach bias might promote the consumption of SSBs. We investigated whether an Approach-Avoidance Training (AAT) reduces this approach bias and related behaviors like craving for and consumption of SSBs. Fifty-six healthy participants, with a self-reported SSB consumption of at least 330 ml per day, were randomized to 6 sessions of real or sham AAT. In the real AAT condition, participants were trained to react with avoidance movements to pictures of SSBs in an implicit learning paradigm (i.e. participants were instructed to respond to a task-irrelevant feature), whereas in the sham AAT condition the same pictures were used but no systematic (avoidance) reaction was trained. Approach bias, craving for SSB and SSB intake in a bogus taste test were assessed. Real AAT was not superior to sham AAT in any outcome measure. AAT in its current form and as a stand-alone intervention does not appear to be effective in reducing SSB consumption.
Gesehen am 07.06.2021